Highly conductive flexible alkylsulfonated side chains poly(phthalazinone ether ketone)s for proton exchange membranes. (18th July 2018) - Jin, Cuihong; Zhu, Xiuling; Zhang, Shuai; Li, Shuai
Abstract: In this work, a series of long flexible alkylsulfonated side chains poly (phthalazinone ether ketone) (SFG-PPEK-x) are successfully synthesized through polycondensation, demethylation, and sulfobutylation grafting reaction to the polymer backbone. The resulting ionomers could dissolve in polar aprotic solvents, such as DMSO, NMP etc and show excellent film-forming properties. Furthermore, the effect of side chain lengths on the properties of the resulting PEMs, such as proton conductivity, water uptake, and swelling ratio are investigated systematically. The SFG-PPEK-4 membranes (IEC = 1.70 mmol g −1 ) show the highest proton conductivity in the range of 107 mS cm −1 at 30 °C and 184 mS cm −1 at 80 °C, which is higher than that of Nafion ® 115. The thermal, mechanical properties and chemical stability of SFG-PPEK-x are discussed, systematically. Graphical abstract: Image 1 Highlights: A series of long flexible alkylsulfonated side chains poly (phthalazinone ether ketone) were synthesized. The effect of chain lengths of alkylsulfonic acid groups on the properties of the resulting polymer PEMs were investigated. The SFG-PPEK-4 membranes (IEC = 1.70 mmol. g −1 ) exhibited excellent proton conductivity as high as 0.184 S cm −1 .